Early adopters boosting the diffusion of sustainable small-scale energy solutions. (June 2015) - Nygrén, Nina A.; Kontio, Panu; Lyytimäki, Jari; Varho, Vilja; Tapio, Petri
Abstract: Local level actors have an important role in developing small-scale energy innovations as well as disseminating the gained knowledge to key audiences. Diffusion of these energy solutions from innovators and early adopters to wider user groups has often been slow. This study explores the innovators׳ and early adopters׳ experiences of their projects, motivations for their behavior, and obstacles that inhibit the diffusion of energy innovations. Four different types of innovators and early adopters of new energy solutions are identified: Enthusiasts, Utilizers, Green Developers and Green Consumers. These groups are characterized by different sets of motivating factors, including environmental concern, interest in technology, economic profit, self-sufficiency, willingness to utilize excess material, promotion of innovations and image reasons. They also have encountered different kinds of barriers to their actions, such as lack of relevant information, poor product quality and lack of economic and institutional support. The different motivating and forestalling factors should be identified and taken into account when developing incentives as well as interaction and communication strategies to enhance the diffusion of innovative, sustainable small-scale energy solutions.